Continental breakup and UHP rock exhumation in action: GPS results from the Woodlark Rift, Papua New Guinea. (11th November 2014) - Wallace, Laura M.; Ellis, Susan; Little, Tim; Tregoning, Paul; Palmer, Neville; Rosa, Robert; Stanaway, Richard; Oa, John; Nidkombu, Edwin; Kwazi, John
Abstract We show results from a network of campaign Global Positioning System (GPS) sites in the Woodlark Rift, southeastern Papua New Guinea, in a transition from seafloor spreading to continental rifting. GPS velocities indicate anticlockwise rotation (at 2–2.7°/Myr, relative to Australia) of crustal blocks north of the rift, producing 10–15 mm/yr of extension in the continental rift, increasing to 20–40 mm/yr of seafloor spreading at the Woodlark Spreading Center. Extension in the continental rift is distributed among multiple structures. These data demonstrate that low‐angle normal faults in the continents, such as the Mai'iu Fault, can slip at high rates nearing 10 mm/yr. Extensional deformation observed in the D'Entrecasteaux Islands, the site of the world's only actively exhuming Ultra‐High Pressure (UHP) rock terrane, supports the idea that extensional processes play a critical role in UHP rock exhumation. GPS data do not require significant interseismic coupling on faults in the region, suggesting that much of the deformation may be aseismic. Westward transfer of deformation from the Woodlark Spreading Center to the main plate boundary fault in the continental rift (the Mai'iu fault) is accommodated by clockwise rotation of a tectonic block beneath Goodenough Bay, and by dextral strike slip on transfer faults within (and surrounding) Normanby Island. Contemporary extension rates in the Woodlark Spreading Center are 30–50% slower than those from seafloor spreading‐derived magnetic anomalies. The 0.5 Ma to present seafloor spreading estimates for the Woodlark Basin may be overestimated, and a reevaluation of these data in the context of the GPS rates is warranted.